2012
DOI: 10.1021/ja2111898
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Oxidative Demethylation: X-ray Crystallographic, Resonance Raman, and UV–Visible Spectroscopic Analysis of a Rieske-Type Demethylase

Abstract: Herein, the structure resulting from in situ turnover in a chemically challenging quaternary ammonium oxidative demethylation reaction was captured via crystallographic analysis and analyzed via single-crystal spectroscopy. Crystal structures were determined for the Rieske-type monooxygenase, stachydrine demethylase, in the unliganded state (at 1.6 Å resolution) and in the product complex (at 2.2 Å resolution). The ligand complex was obtained from enzyme aerobically cocrystallized with the substrate stachydrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 90 publications
0
82
1
1
Order By: Relevance
“…However, recent bioinfomatic and evolutional analyses suggest that Rieske-type proteins are much more diverse than previously thought (38)(39)(40). Indeed, eukaryotic Rieske-type terminal oxygenases have also been identified [e.g., choline monooxygenase (41,42)], and recent studies have confirmed that Rieske-type proteins can carry out nonring hydroxylation reactions, such as oxidative demethylation (43) and oxidative carbocyclization (44). Furthermore, many novel Riesketype proteins have been identified with no assigned function, many of which originated from newly sequenced microbial genomes (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent bioinfomatic and evolutional analyses suggest that Rieske-type proteins are much more diverse than previously thought (38)(39)(40). Indeed, eukaryotic Rieske-type terminal oxygenases have also been identified [e.g., choline monooxygenase (41,42)], and recent studies have confirmed that Rieske-type proteins can carry out nonring hydroxylation reactions, such as oxidative demethylation (43) and oxidative carbocyclization (44). Furthermore, many novel Riesketype proteins have been identified with no assigned function, many of which originated from newly sequenced microbial genomes (38).…”
Section: Resultsmentioning
confidence: 99%
“…5B). It is interesting to note that the glutamate residue is found in at least two other enzymes of the Rieske-type protein family, dimethylproline demethylase (Stc2) (43) and GBT demethylase (GbcA) (50), although no further data were available on the role of this residue in these proteins. Our study therefore suggests that caution needs to be taken when interpreting structure-function relationships of Rieske-type proteins using existing structures that are dominated by ring-hydroxylating oxygenases.…”
Section: Deletion Ofmentioning
confidence: 99%
“…(21). Of particular note is the configuration of the bridging acidic residue; in ROs in which the Rieske cluster is reduced, such as OMO red (21) and stachydrine demethylase (Stc2) (44), the carboxylate bridges the ligands of the metallocenters. Nevertheless, it is unclear why the KshA Rieske clusters would be oxidized because the x-ray beam is expected to reduce the clusters (45).…”
Section: Discussionmentioning
confidence: 99%
“…UV-visible diffuse reflectance spectroscopy is one technique that can b extent of reduction of fully-oxidized catalysts by exposing them to a bro visible wavelengths [14,[16][17][18][19][20][21][22]. While XANES/EXAFS studies require h synchrotron sources, UV-visible spectroscopy is easily performed in the Operando UV-visible spectroscopy can provide new insight on surface elect has potential as a new method to determine the extent of reduction of a fully affects the absorbance of light by the catalyst surface [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%